The associations among the ethical climate, the professional practice environment and individualized care in care settings for older people - Suhonen, Riitta A.; Stolt, Minna; Gustafsson, Marja Liisa; Katajisto, Jouko; Charalambous, Andreas (My University, 2014)
Aim: To investigate the associations among the ethical climate, professional practice environment and individualized nursing care in care settings for older people. Background: The quality of care provision is affected by organizational environments, such as ethical climate and professional practice environment. Although, the association between professional practice environment and individualized nursing care has been pointed out, we know that little is known about how ethical climate is associated with the level of individualized nursing care delivery. Design: A cross-sectional explorative and correlational survey design. Methods: The study was conducted in 62 units in the vicinity of a Finnish city using a sample of nurses (N = 874, response rate 58%) who worked clinically with older people in different care settings in 2012. Survey data were collected using the Hospital Ethical Climate Survey, Revised Professional Practice Environment scale and Individualised Care Scale-B. Data were analysed statistically using descriptive statistics, correlation coefficients (Pearson) and multiple stepwise regression analyses. Results: Statistically significant correlations were found among the variables, ethical climate and individualized care and between individualized care and all professional practice environment sub-scales. Multiple stepwise regression showed associations among individualized care, ethical climate and internal work motivation, control over practice and leadership and autonomy. Conclusions: The study provided better understanding of the complex concept of individualized care by taking into consideration the ethical climate and the practice environment and their associations. To increase individualization in care provision, efforts need to be directed towards organizational aspects requiring the support of nursing leaders.
Keywords: Ethical climate; Individualized care; Nurse; Older people care; Professional practice environment; Survey